Prosedur Penyandaran Kapal Sandar Tender oleh PT. Berlian Ocean Shipping Dumai di Dermaga Kawasan Indutri Dumai - Sabila, Fadiyah Hani; Sinaga, Rodenson (Majalah Ilmiah Gema Maritim, 2023)
PT. Berlian Ocean Shipping Dumai is one of the shipping companies engaged in shipping agencies that recognizes local and foreign ships. As with the activities of shipping companies in general, PT. Berlian Ocean Shipping Dumai also provides the same service, which serves every ship need starting from ship arrival plans, ship docking, supplying ship and crew needs, managing crew sign-on and sign-off, handling goods documents, extending ship certificates, managing the issuance of Sailing Approval Letters (SPB) to ship departure. The docking procedure for this tender berthing ship is very important to understand, where every ship that will carry out unloading or loading activities must dock and be moored at the dock. To create effective, safe, smooth and efficient docking and departure, the implementation must be by predetermined regulations, good communication and good cooperation in carrying out the berthing of tender berths. PT. Berlian Ocean Shipping Dumai always strives to provide the best service to principals, including making plans to ensure that there are no significant errors during implementation, both in terms of handling ship documents and obtaining permits through the system as well as in docking and departing ships. In every field of work, of course, various difficulties and risks will be faced. Thus in docking and departing ships, it must be handled by professional labor, because considering the impact that may occur and can cause delays to the carrier if it makes a mistake in the movement of the ship (docking and departure of the ship).